The customs areas of the world - United Nations (New York, 1959)
The descriptions contained in this paper are based largely on official information supplied by Governments.
United Nations. [Document] ST/STAT/ser.M/30.
"United Nations publication. Sales no.: 59.XVII.5."
osc 16/08/2018
Loans
Keywords: Customs administration